A critical analysis of Resolution 1117/19 of the Organization of American States Permanent Council declaring illegitimate the Presidency of Nicolás Maduro of Venezuela - De Wet, Erika (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.